The spirit level : why greater equality makes societies stronger - WILKINSON, Richard G.; Pickett, Kate. (New York : Bloomsbury Press, 2010)
This eye-opening UK bestseller shows how one single factor--the gap between its richest and poorest members--can determine the health and well-being of a society. The authors also outline a new political outlook in which a shift from self-interested consumerism to a friendlier, more sustainable society is paramount.
Material success, social failure. The end of an era -- Poverty or inequality? -- How inequality gets under the skin -- The costs of inequality. Community life and social relations -- Mental health and drug use -- Physical health and life expectancy -- Obesity: wider income gaps, wider waists -- Educational performance -- Teenage births: recycling deprivation -- Violence: gaining respect -- Imprisonment and punishment -- Social mobility: unequal opportunities -- A better society. Dysfunctional societies -- Our social inheritance -- Equality and sustainability -- Building the future.
First published in Great Britain by Allen Lane, 2009.
Includes bibliographical references (p. 271-297) and index.
Keywords: Equality; Social mobility; Quality of life; Social policy